Applying Semantic Mapping to Improve Students’ Reading Comprehension - Luana Sasabone (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2018)
Reading is one of the essential skills in learning English. However, numerous English learners still find difficult to comprehend English texts. Therefore, it is importance to renders students an effective strategy to learn reading. The aim of the study were to find out to the extent to the use of the semantic mapping improve students’ reading comprehension. This study applied a quasi-experimental design. The subjects of the research were the first semester students of Law Faculty class selected purposely. The data collection was done by utilizing TOEFL reading test. The data were analyzed using SPSS version 21 IBM in order to obtain the frequency, mean score, normality test, and nonparametric test (Mann-Whitney U test and Wilcoxon test). The results indicate that the application of the semantic mapping to teach reading contributes to the students’ reading achievement. The result of the Man-Whitney U test demonstrated that there was a significant difference between the mean score of experimental group with the semantic mapping, and controlled group without semantic mapping(42.3 > 32.3). Meanwhile, Wilcoxon test showed that experimental group performed significant difference between pretest (29.5) and posttest (42.3). It may be inferred that the semantic mapping contributes to the enhancement of students’ reading comprehension.